The cross-culture impact on managing business: an evidence from culture, performance evaluation practices, and trust in a Western Multinational Company’s subsidiary in Indonesia - Unggul Purwohedi (Jurnal Ilmiah Wahana Akuntansi, 2013)
ABSTRACT The purpose of this study is to investigate the cross-cultural influence on organizational practices, performance evaluation process and trust on supervisors in a Multinational Company (MNC) in Indonesia. Amongst studies of national culture and MNCs there appears to have been no studies investigating the interaction between cross-culture, performance evaluation, and trust. Therefore, I conducted a case study research in one French MNC in Indonesia to understand this process. I interviewed 13 staff from the country president down to front-line employees. I used Leximancer V3.5 to help identify a number of emerging themes and concepts. The people theme is the most important and comprises concepts such as trust, review, relationship, and performance. In addition, I found four cultural issues between expatriates and local subordinates: sense of belonging, hierarchy, performance evaluation, and trust. Furthermore, in order to understand the specific area, I did analysis across the strategic business units, functions, and organization level in our case study company. Key Words: Cross-culture, Multinational company, Performance evaluation, Trust